2016
DOI: 10.1111/ane.12636
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid and blood flow patterns in idiopathic normal pressure hydrocephalus

Abstract: The typical flow of blood and CSF in INPH was mainly characterized by increased CSF pulsatility in the aqueduct and reduced cervical CSF pulsatility. The direction of mean net aqueduct CSF flow was from the third to the fourth ventricle. Our findings may reflect the altered distribution of intracranial CSF volume in INPH, although the causality of these relationships is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 35 publications
5
41
0
Order By: Relevance
“…8,14,[19][20][21] Our finding was similar with four of them reporting a net flow in the direction of caudalcranial regarding iNPH patients. It showed that there was small volume of CSF flow from the forth ventricle to lateral and third ventricles at the end of a CSF flow cycle in iNPH patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…8,14,[19][20][21] Our finding was similar with four of them reporting a net flow in the direction of caudalcranial regarding iNPH patients. It showed that there was small volume of CSF flow from the forth ventricle to lateral and third ventricles at the end of a CSF flow cycle in iNPH patients.…”
Section: Discussionsupporting
confidence: 90%
“…It showed that there was small volume of CSF flow from the forth ventricle to lateral and third ventricles at the end of a CSF flow cycle in iNPH patients. 21 Note that the pixel size used in that study was 1.2×1.2 mm, which was the highest resolution among all the five studies. 8,14,[19][20][21] Our finding was similar with four of them reporting a net flow in the direction of caudalcranial regarding iNPH patients.…”
Section: Discussionmentioning
confidence: 95%
“…The CA ( Figure 5A) and SS ( Figure 5B) flow curves were integrated to yield stroke volume (mm 3 ), which represents the total displacement of CSF in the rostral and caudal direction over the cardiac cycle. 5,8,42,45,46 The maximum and minimum points on the flow curve were used to represent the flush and fill peak (mm 3 /s), respectively. 41,45,47,48 The delay between the beginning of the flow curve and the maximum and minimum points were represented as the time-to-flush and timeto-fill peak (%CC), respectively.…”
Section: Calculation Of Flow Parametersmentioning
confidence: 99%
“…PC measurements perpendicular to the aqueduct also allow quantitative evaluation of CSF pulsation through the aqueduct [18]. The diagnostic value of these examination methods is controversial in the literature [19,20]. An overview of the diagnostic criteria [12,21] of hydrocephalus is provided in ▶ Table 2.…”
Section: Examination Methods and Morphological Imaging Criteria Of Hymentioning
confidence: 99%
“…Impaired CSF dynamics can be visualized and quantified with the help of phase contrast scans [38]. However, the relevance of these findings for diagnosis and the prediction of treatment response is controversial in the literature [19,20].…”
Section: Idiopathic Normal Pressure Hydrocephalusmentioning
confidence: 99%